PENGARUH KUALITAS PRODUK DAN CITRA MEREK PADA KEPUTUSAN PEMBELIAN LAPTOP MEREK ASUS DI KALANGAN MAHASISWA DI KOTA SURABAYA - Fitrah Fitrah; Is Fadhillah (Jurnal Bina Bangsa Ekonomika, 2023)
This study is to find out more about "Product Quality and Brand Image on Purchasing Decisions for Asus Laptops for Surabaya Students". The variety of laptop products available today encourages consumers, especially students in the city of Surabaya, to be more selective in making purchasing decisions by knowing when a laptop brand meets the criteria as an ideal laptop product. Asus is one of the trusted electronics manufacturers in Indonesia that has produced a variety of products and is a brand of pride for its consumers. The research method used is quantitative with a sampling technique of ten using non probability, the number of respondents is 100 people with purposive sampling technique. The data analysis technique in this study uses multiple linear regression analysis. The hypothesis was tested with the T test and F test. The test results show that product quality has a negative or insignificant effect on purchasing decisions for asus laptops for Surabaya students, while brand image has a positive or significant effect on purchasing decisions for asus laptops for Surabaya students. Together (simultaneously) product quality and brand image have an influence of 67% on purchasing decisions for asus laptops for students in Surabaya